TRANSFORMATION OF THE COLLECTIVE MEMORY. THE IDEOLOGICAL FUNCTION OF THE UKRAINIAN INSTITUTE OF NATIONAL MEMORY IN 2014-2017 - Minakov, Minakov (Porównania, 2019)
Mikhail Minakov, TRANSFORMATION OF THE COLLECTIVE MEMORY. THE IDEOLOGICAL FUNCTION OF THE UKRAINIAN INSTITUTE OF NATIONAL MEMORY IN 2014-2017. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 31-43. ISSN 1733-165X. The post-Euromaidan’s Ukraine has developed in a contradictory way: together with democratization and Europeanization, there was also a spread of conservative ideologies and limitation of civic freedoms. The latter tendencies were connected with the attempts at establishing ideological monopoly— a system of ideological control that existed in USSR and disappeared in the decommunization processes of 1989-91—in the interests of nowadays’ ruling groups. One of those institutions adding to the possibility of revival of the ideological monopoly is the Ukrainian Institute of National Memory. In this paper, the author argues that after several reforms between 2006 and 2018, the Institute evolved into a state body providing conservative cultural policies and illiberal identity policies undermining Ukraine’s civic democratic consolidation. Based on the analysis of the Institute’s political role and achievements so far, the author concludes that the current cultural policies and organizational practices of the Institute (and similar organizations) have created a new post-Soviet ideological toolkit enabling power elites to effectively establish conservative ideological monopoly in Ukraine.